The Role of Social Media in Increasing Public Trust in the Government in Parepare - Genda, Silahuddin (Journal Social Civilecial, 2025)
Researchers conduct a study that evaluates how social media affects public trust in local government through a specific analysis of Parepare in South Sulawesi. A quantitative study analyzes the effects that the mayor's social media presence generates on resident's perceptions about government transparency and their trust levels. Four hundred residents were surveyed to analyze the frequency and variety of information shared by the mayor across Facebook Twitter and Instagram alongside their effect on public trust levels. Social media activity by the mayor results in higher public trust for local government according to 64% of respondents who believe the city became more transparent because of social media use. The municipality received the most favorable response to content focusing on government initiatives and public participation with 50% acceptance and 30% positive reaction. The results showed that trust levels increased uniformly in proportion to education level because people with higher education demonstrated stronger trust associations. These research outcomes support previous studies about how social media helps government agencies become transparent and engage the public yet stress the requirement for improved local communication methods. This research study addresses the lack of existing literature about social media use within local governments in lower-politicized regions while presenting applicable suggestions to build public trust in local governance.